Postnatal Low Protein Diet Programs Leptin Signaling in the Hypothalamic-Pituitary-Thyroid Axis and Pituitary TSH Response to Leptin in Adult Male Rats - Lisboa, P. C.; Oliveira, E.; Fagundes, A.T. S.; Santos-Silva, A. P.; Conceição, E.P. S.; Passos, M.C. F.; Moura, E. G. (Hormone and Metabolic Research, 2012)
Maternal protein restriction (PR) during lactation programs a lower body weight, hyperthyroidism, leptin resistance, and over-expression of leptin receptor in the pituitary gland at adulthood. Because leptin regulates energy homeostasis and the hypothalamus-pituitary-thyroid (HPT) axis, we evaluated adipocyte morphology, the leptin signaling pathway in the HPT axis and the in vitro thyrotropin (TSH) response to leptin in adult progeny in this model. At birth, dams were separated in control diet with 23% protein or PR diet with 8% protein. After weaning, offspring received a normal diet. Adult PR offspring showed lower adipocytes area, higher leptin:visceral fat ratio, lower hypothalamic signal transducer and activator of transcription 3 (STAT3), higher pituitary leptin receptor (Ob-R) and lower thyroid janus tyrosine kinase 2 (JAK2) contents. Regarding the in vitro study, 10 − 7  M leptin stimulated TSH secretion in C offspring at 30 min, but had no effect in PR offspring. At 120 min, 10 − 7  M leptin decreased TSH secretion in C offspring and increased in PR offspring. Maternal nutritional status during lactation programs for adipocyte atrophy, higher relative leptin secretion and changes in the downstream leptin signaling in the HPT axis and the TSH response to leptin, suggesting a role for leptin in the development of the HPT axis and helping to explain thyroid dysfunction and leptin resistance in this programming model. Because leptin stimulates thyroid function, it is unlikely that these alterations were responsible for the increased in serum T4 and T3. Therefore, neonatal PR programs a hyperthyroidism, lower adipogenesis, and impairment of leptin action.
Keywords: developmental programming; leptin; TSH